Training for growth: Skills shortage and companies' willingness to train in Colorado. An application of the KOF Willingness to Train Survey - Ursula Renold; Thomas Bolli; Katherine Caves; Jutta Buergi (ETH Zurich, KOF Swiss Economic Institute, 2017)
This report analyzes KOF Willingness to Train Survey responses from up to 377 companies in Colorado to understand the current situation of skills and how companies train to produce more skills when necessary. It also assesses how Colorado's stakeholders cooperate and interact to facilitate training. Finally, we report what companies want from new training programs and give recommendations for how those can be constructed to reduce the skill shortage for companies and provide workers with the skills they need to succeed on the labor market. This section summarizes our main findings.
Keywords: 330